Perancangan Model Data Warehouse dan Perangkat Analitik untuk Memaksimalkan Proses Pemasaran Hotel: Studi Kasus pada Hotel Abc - Miranda, Eka (ComTech: Computer, Mathematics and Engineering Applications, 2013)
The increasing competition in hotel business forces every hotel to be equiped with analysis tools that can maximize its marketing performance. This paper discusses the development of a data warehouse model and analytic tools to enhance the company's competitive advantage through the utilization of a variety of data, information and knowledge held by the company as a raw material in the decision making process. A study is done at ABC Hotel which uses a database to save the transactional record. However, the database cannot be directly used to support analysis and decision making process. Based on this issue, the company needs a data warehouse model and analytic tools that can be used to store large amounts of data and also potentially to gain a new perspective of data distribution which allows to provide reporting and answers of ad hoc users questions and assist managers in making decisions. Further data warehouse model and analytic tools can be used to help manager to formulate planning and marketing strategies. Data are collected through interviews and literature study, followed by data analysis to analyze business processes, to identify the problems and the information to support analysis process. Furthermore, data warehouse is designed using analysis of records related to the activities in hotel's marketing area and data warehouse model. The result of this paper is data warehouse model and analytic tools to analyze the external and transactional data and to support decision making process in marketing area.